Dilema Bioetika dalam Praktik Biohacking Berbasis RFID (Lembaga Pengembangan Kinerja Dosen, 2026)
RFID (Radio Frequency Identification)-based biohacking has evolved as a body modification practice that integrates technology directly into human biology. While the practice has historical roots dating back to World War II when RFID was used to identify aircraft, its development toward human implantation began in the late 20th century and has become more widespread with society's increasing reliance on digital technology. Analysis of the principle of beneficence reveals that although RFID implantation can increase user convenience, comfort and security, these benefits are not yet fully supported by adequate scientific evidence regarding long-term safety. Meanwhile, the principle of non-maleficence highlights the risks of infection, tissue damage, interference with radiological examinations, and publications regarding other medical complications resulting from implantation, which is generally performed by non-medical personnel. Through historical, technical, and ethical reviews, this research emphasizes the need for a clearer regulatory framework, increased bioethical literacy, and the involvement of healthcare professionals in implantation to ensure that technological developments do not compromise human safety and well-being